Traffic flow at signalized intersections with large volumes of bicycle traffic. (January 2022) - Grigoropoulos, Georgios; Leonhardt, Axel; Kaths, Heather; Junghans, Marek; Baier, Michael M.; Busch, Fritz
Abstract: The popularity of utilitarian bicycling is increasing in many urban areas. As a result, growing volumes of bicycle traffic on road networks have significant impacts on traffic flow and the capacity of vehicular traffic, particularly at intersections. The goal of this paper is to quantify the impact of large volumes of bicycle traffic on the capacity of signalized intersections concerning vehicular streams crossing the intersection, turning right, and turning left. Empirical studies are conducted to gain insight into the speed, acceleration, queue density, queue discharge, and conflict zone occupancy time of bicycle traffic. Data were collected at sites with varying infrastructure designs and bicycle traffic volumes. The results of the empirical studies are used to assess the effects of bicycle infrastructure on traffic efficiency and build, calibrate, and validate microscopic traffic simulation models. The bicycle traffic volume is incrementally increased in the simulation models to supplement the data from the empirical studies. Based on the empirical findings and simulation results, the average queue discharge time per bicyclist based on the facility width is derived and two factors for the reduction in the capacity of vehicular traffic turning left and turning right based on the actual green time ratio and the volume of crossing bicycle traffic are proposed. If a bike box is present on an intersection approach, findings show that crossing bicycle traffic has a negligible effect on the capacity of crossing vehicular traffic, which bicyclists turning left impede vehicular traffic.